Efektivitas Media Video Tutorial Untuk Meningkatkan Keterampilan Membuat Puding Karamel Bagi Anak Disabilitas Intelektual Ringan - Marwah Adelita; Zulmiyetri Zulmiyetri; Rahmahtrisilvia; Antoni Tsaputra (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
This study aims to describe changes in the ability to make caramel pudding in children with mild intellectual disabilities after being taught using video tutorial media. The study used a quantitative approach with the Single Subject Research (SSR) method with an A-B design consisting of a baseline (A) and intervention (B) phase. The study was conducted on May 11–26, 2026 at SLB Serasi Payakumbuh. The research subject was selected purposively, namely one 11th grade student with mild intellectual disabilities who experienced difficulties in making caramel pudding skills. Data were collected through performance observations, practical tests, and documentation, then analyzed using visual analysis within conditions and between conditions that include the direction of trends, levels of stability, level changes, and percentage of overlap. The results showed that the subject's abilities increased after being given intervention using video tutorials. In the baseline phase, skill achievement remained at 50% for three sessions, while in the intervention phase it increased to 78%, 78%, 83%, 83%, 83%, and 83% for six sessions. These findings indicate a change in the ability to make caramel pudding after the application of video tutorial media to the research subjects. Thus, video tutorial media has the potential to be used as an alternative for learning vocational skills for students with mild intellectual disabilities, although the findings of this study are limited to the characteristics of the subjects studied.